234k views
22 votes
Im on the seacond part 2 more to go lol

Im on the seacond part 2 more to go lol-example-1
User Andy Dang
by
5.7k points

2 Answers

10 votes

Answer:

see below

Explanation:

2p + 8 = 20 - p

add p to both sides

2p + p + 8 = 20 - p + p

combine like terms

3p + 8 = 20

subtract 8 from both sides

3p + 8 - 8 = 20 - 8

combine like terms

3p = 12

divide both sides by 3

3p / 3 = p

12/3 = 4

we're left with p = 4

User Alirobe
by
5.9k points
4 votes

Answer:

p = 4

Explanation:

3p + 8 = 20

3p = 20 - 8

3p = 12

p = 12/3

p = 4

User ReneS
by
5.6k points